Influência da parametrização de turbulência na simulação numérica de propagação de microbursts - (:unkn) unknown (Universidade Federal do Pampa, 2020)
The microburst phenomenon is characterized as a strongly localized downdraft, producing intense highly-divergent winds close to the surface, resulting in different wind speed profiles than those typically observed in the atmospheric boundary layer. Such characteristics make the phenomenon one of the main topics for studies of structural analysis in engineering. Therefore, the initial objective in this work is the implementation of the cooling source model introduced by Anderson, Orf e Straka (1992) for microbursts analysis in the OpenFOAM software. After implementing the proposed model, it is observed that it presents the outflow characteristics of a real microburst. In a second step, the influence of different turbulence parameterizations on the formation and propagation of the microburst wavefront is investigated. The turbulence parameterizations used consist of two linear and one nonlinear models, which are part of the SOWFA toolset. Similarities were found between linear models, regarding development and diffusivity in front of the wave, as well as the occurrence of maximum speeds at high altitudes. The nonlinear model showed lower diffusivity in front of the wave during propagation, with the maximum velocities concentrating at lower levels than the other models. Therefore, it is demonstrated that there is influence of the different turbulence parameterizations on the propagation of microbursts.
Keywords: Engenhariaq; Microburst; Ondas (Física); Engineering; Waves; CNPQ::ENGENHARIAS